2017
DOI: 10.1109/lawp.2016.2600525
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Small, Broadside Radiating Huygens Source Antenna Augmented With Internal Non-Foster Elements to Increase Its Bandwidth

Abstract: Abstract-A broadside radiating, linearly polarized, electrically small Huygens source antenna system that has a large impedance bandwidth is reported. The bandwidth performance is facilitated by embedding non-Foster components into the near-field resonant parasitic (NFRP) elements of this metamaterial-inspired antenna. High quality and stable radiation performance characteristics are achieved over the entire operational bandwidth. When the ideal non-Foster components are introduced, the simulated impedance ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 18 publications
(22 reference statements)
1
61
0
Order By: Relevance
“…The previously discussed cases have provided further insights into the electrically small, low-profile broadside radiating, Huygens source antennas [22][23][24]. The configuration of interest is shown in Figure 19.…”
Section: Multiple Nfrp Element Huygens Source Antennamentioning
confidence: 92%
See 3 more Smart Citations
“…The previously discussed cases have provided further insights into the electrically small, low-profile broadside radiating, Huygens source antennas [22][23][24]. The configuration of interest is shown in Figure 19.…”
Section: Multiple Nfrp Element Huygens Source Antennamentioning
confidence: 92%
“…On the other hand, recent designs have suggested that Huygens sources may be advantageous, particularly in regards to their FTBR values [20][21][22][23][24][25]. Consequently, it was explored whether or not the magnetic-based EZ antenna could be augmented with an electric-based NFRP antenna to achieve an electrically small Huygens source.…”
Section: D Magnetic Ez Antennamentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, the Federal Communications Commission (FCC) of the US has recently (July 2016) designated the frequency band from 27.5 to 28. 35 GHz for 5G applications [2]. Another 5G breakthrough concept is the introduction of Device-to-Device (D2D) communications.…”
Section: Introductionmentioning
confidence: 99%